Qualidade fisiológica de sementes de soja sob estresse em pós-semeadura em solo seco - Santos, Cassiano Vasconcelos dos (2021)
Seeding in dry soil is the practice of placing the seed in the soil with low humidity before precipitation occurs, in this way, the seeds are stored in the soil, exposed to hydric and thermal stress, pests attack and diseases, while waiting for moisture conditions to begin the germination process. The use of quality seeds is a very important practice for the production system, because there is an increase in the germination percentage, normal seedlings and vigor. Therefore, this study aims to evaluate the effects of seeding in dry soil and exposure to stress periods on the physiological quality of soybean seeds. Thus, two different experiments were carried out. The first experiment, aimed to evaluate the effects that drought periods after seeding in dry soil have on the physiological quality of seeds and the action of soil vegetation coverage as a possible stress reliever. To simulate periods of hydric stress, two seed batch remained in the soil without irrigation for 0, 4, 8, 12 and 16 days, after seeding in the pots, these pots had or not a ground cover with black oat straw. The assessment were made from emergence to the beginning of the reproductive stage of crop. Vigor effects provide greater emergency and faster establishment in sowing conditions under hydric stress and they are more expressive in the early stages of germination and establishment, and less obvious as the phenological stages progress. Storage in dry soil within 4 days does not affect emergency, which is reduced from 8 to 16 days of storage with equal intensity. Vegetation coverage of the soil enables greater emergency and initial growth in relation to the bare ground, improving the establishment and plant stand. The second experiment had goal to evaluate effects of temperature and period in days that the seeds were stored in dry soil under their physiological quality and the consequences on the germination process and post-germination development in soybean seeds. Seeds were sown in trays and stored for periods of 0, 7, 14 and 21 days in the soil without moisture and placed in a BOD germinator with controlled temperature of 15, 25 and 35 ºC. After storage, the dry soil was irrigated, raising its moisture to 60% of its retention capacity and keep the BODs at 25 ºC and constant light during germination. Five days after irrigation, emergency, seedling classifications as normal, abnormal and dead, length and dry mass were evaluated. In addition, digitalization was performed using images of the seedlings for further analysis. Seeding in dry soil for up to 21 days of storage at a temperature of 35 ºC does not affect the physiological quality of soybean seeds, it was also observed that storage at lower temperatures can result in more heterogeneous results and be harmful to seed performance.